Nepotisme dalam Perspektif Tafsir Kontemporer dan Klasik: (Tela’ah Interprestasi dengan Pendekatan Hermeneutika Hassan Hanafi) - Ellyatus Sholihah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This research investigates the topic of nepotism in the Qur'an by placing special emphasis on Hassan Hanafi's method of analysing verses attributed to nepotism. In this case, the research uses a Library Research approach to investigate Hanafi's perspective on nepotism. This research aims to add to the literature studying the concept of nepotism in the Qur'an by providing interpretations from three phenomenal mufassirs in Qur'anic research. It is hoped that the results will allow for a deeper discussion and understanding of the rejection of nepotism in Qur'anic interpretation, especially in light of the changes taking place in modern society.